Habiter en écovillage, une [éco]utopie du xxie siècle ? - Sylvia Amar (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Numerous initiatives are mobilizing to make the Earth a better place to live. Positioned as alternatives to urban life, intentional communities and/or ecovillages are now among the most dynamic and structured. Since the late 1990s, projects have been multiplying worldwide, continuing the evolution of an ancient movement into a flourishing international network active on multiple fronts. In the face of growing discourse on ecological issues, their concrete actions are particularly relevant to observe, especially in the context following the COVID-19 global health crisis. To present the holistic dimension of their approach, the paper draws on socio-spatial constructions implemented by four ecovillages currently in operation: La Cité écologique (Canada/United States), Torri Superiore (Italy), Hallingelille (Denmark) and Hameau des Buis (France). While each of these experiences is unique, they all converge on several points: a willingness to integrate their lifestyle choices into an ecological and educational approach connected to their local territory, a foundation of shared values worldwide facilitated by digital tools, and a desire to associate the basis of their social project with the construction of architectures capable of embodying it and supporting its perfectible dimension. Lastly, because it is part of a history of architectural utopias intersecting with that of environmental struggles, their quest allows for a perspective on contemporary eco-habitation issues. Living, Experimenting, Building are the axes proposed to present the cited case studies and highlight their ability to act on reality, even on very small scales.